Similarity Between Room Layouts Causes Orientation-Specific Sensorimotor Interference in To-Be-Imagined Perspective Switches - Riecke, B. E.; McNamara, T.P. (48th Annual Meeting of the Psychonomic Society (Psychonomics), 2007)
May (2004) suggested that the difficulty of imagined perspective switches is partially caused by interference between the sensorimotor (actual) and to-be-imagined orientation. Here, we demonstrate a similar interference, even if participants are in a remote room and dont know their physical orientation with respect to the to-beimagined orientation. Participants learned 15 target objects located in an office from one orientation (0, 120, or 240). Participants were blindfolded and disoriented before being wheeled to an empty test room of similar geometry. Participants were seated facing 0, 120, or 240, and were asked to perform judgments of relative direction (e.g., imagine facing "pen", point to "phone"). Performance was facilitated when participants to-be-imagined orientation in the learning room was aligned with the corresponding orientation in the test room. This suggests that merely being in an empty room of similar geometry can be sufficient to automatically reanchor ones representation and thus produce orientation-specific interference.
Keywords: Riecke; Riecke_2007; bernhard-riecke; egocentric; frame; framework; iSpaceWeb; interference; model; orientation; proj--McNamara-JRD-RW-refFrames; proj--Moura2009-JRDInVR; reference; spatial; spatial-cogn-vr-rw; talkWithoutPaper; theory; timothy-mcnamara; updating